2020
DOI: 10.1021/acsomega.0c04117
|View full text |Cite
|
Sign up to set email alerts
|

Promising Rice-Husk-Derived Carbon/Ni(OH)2Composite Materials as a High-Performing Supercapacitor Electrode

Abstract: Improving the electrochemical performance of biomass-derived carbon electrode-active materials for supercapacitor applications has recently attracted considerable attention. Herein, we develop hybrid electrode materials from rice-husk-derived porous carbon (RH-C) materials and β-Ni­(OH)2 via a facile solid-state reaction strategy comprising two steps. The prepared RH-C/Ni­(OH)2 (C–Ni) was investigated using scanning electron microscopy (SEM) (energy-dispersive X-ray spectrometer (EDS)), X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Particularly, the unique crystal structure of biomass-based carbon materials determines the rapid transport of electrolyte ions in electrodes, which makes them very promising supercapacitor electrode materials . Substantial studies have demonstrated biomass-based carbonaceous materials as a competitive raw material in supercapacitor applications, such as paddy, banana leaves, rice husk, garlic seeds, dragon fruit peels, oak seeds, etc. Among all biowaste-based carbonaceous materials, AC fabricated from a lignocellulosic precursor is preferable because of its large specific surface area, tunable porosity, high chemical stability, and good electrical conductivity. , As an easily available and inexpensive lignocellulosic biomass, coconut shell (CS) is an ideal precursor of AC for supercapacitor electrodes. …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the unique crystal structure of biomass-based carbon materials determines the rapid transport of electrolyte ions in electrodes, which makes them very promising supercapacitor electrode materials . Substantial studies have demonstrated biomass-based carbonaceous materials as a competitive raw material in supercapacitor applications, such as paddy, banana leaves, rice husk, garlic seeds, dragon fruit peels, oak seeds, etc. Among all biowaste-based carbonaceous materials, AC fabricated from a lignocellulosic precursor is preferable because of its large specific surface area, tunable porosity, high chemical stability, and good electrical conductivity. , As an easily available and inexpensive lignocellulosic biomass, coconut shell (CS) is an ideal precursor of AC for supercapacitor electrodes. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, composites with high surface‐area conductive materials such as CNTs, activated carbon, graphene, show remarkably enhanced electrochemical performance due to improved electrical conductivity of the composites, and the shortening of the electron and ion diffusion pathways. [ 173 , 174 , 175 , 176 ]…”
Section: Components Of Textile‐based Supercapacitorsmentioning
confidence: 99%
“…Thus, composites with high surface-area conductive materials such as CNTs, activated carbon, graphene, show remarkably enhanced electrochemical performance due to improved electrical conductivity of the composites, and the shortening of the electron and ion diffusion pathways. [173][174][175][176] Cobalt oxide (Co 3 O 4 ) is generally considered one of the best candidates for electrode material in the field of SCs owing to its superior reversible redox behavior, excellent cycle stability, large surface area, and outstanding corrosion stability. [177][178][179] The redox reactions in alkaline electrolyte solution can be expressed as follows:…”
Section: Metal Oxidesmentioning
confidence: 99%
“…[105] Additionally, Nickel hydroxide [Ni(OH) 2 ] is another attractive electrode material for supercapacitors due to its high theoretical capacity and superior redox behavior. [106,107] Furthermore, Cobalt oxide (Co 3 O 4 ) also possesses superior reversible redox behavior, excellent cycle stability, large surface area, and outstanding corrosion stability, [108][109][110] thus another suitable electrode material for supercapacitor electrodes. Due to its layered structure with a large interlayer spacing, Cobalt hydroxide [Co(OH) 2 ] provides a large surface area with a high ion insertion/extraction rate offering a great potential to become a high-performance electrode material [98] specifically for energy storage studies.…”
Section: Metals and Their Oxidesmentioning
confidence: 99%